Improving measures of access to legal abortion: A validation study triangulating multiple data sources to assess a global indicator - Williams, C.R.; Va´zquez, P.; Nigri, C.; Adanu, R.M.; Bandoh, D.A.B.; Berrueta, M.; Chakraborty, S.; Gausman, J.; Kenu, E.; Khan, N.; Langer, A.; Odikro, M.A.; et al. (PLOS ONE, 2023)
Background Global mechanisms have been established to monitor and facilitate state accountability regarding the legal status of abortion. However, there is little evidence describing whether these mechanisms capture accurate data. Moreover, it is uncertain whether the “legal status of abortion” is a valid proxy measure for access to safe abortion, pursuant to the global goals of reducing preventable maternal mortality and advancing reproductive rights. Therefore, this study sought to assess the accuracy of reported monitoring data, and to determine whether evidence supports the consistent application of domestic law by health care professionals such that legality of abortion functions as a valid indicator of access. Methods and findings We conducted a validation study using three countries as illustrative case examples: Argen tina, Ghana, and India. We compared data reported by two global monitoring mechanisms (Countdown to 2030 and the Global Abortion Policies Database) against domestic source documents collected through in-depth policy review. We then surveyed health care professionals authorized to perform abortions about their knowledge of abortion law in their countries and their personal attitudes and practices regarding provision of legal abortion. We compared professionals’ responses to the domestic legal frameworks described in the source documents to establish whether professionals consistently applied the law as written. This analysis revealed weaknesses in the criterion validity and construct validity of the “legal status of abortion” indicator. We detected discrepancies between data reported by the global monitoring and accountability mechanisms and the domestic policy reviews, even though all referenced the same source documents. Further, provider surveys unearthed important context-specific barriers to legal abortion not captured by the indicator, including conscientious objection and imposition of restrictions at the provider’s discretion. Conclusions Taken together, these findings denote weaknesses in the indicator “legal status of abortion” as a proxy for access to safe abortion, as well as inaccuracies in data reported to global monitoring mechanisms. This information provides important groundwork for strengthening indicators for monitoring access to abortion and for renewed advocacy to assure abortion rights worldwide.
Research Article